Impact of modified techniques on outcomes of peroral endoscopic myotomy: A narrative review - Nabi, Zaheer; Nageshwar Reddy, D. (Frontiers in Medicine, 2022)
Per-oral endoscopic myotomy (POEM) has been established as a frontline treatment modality for achalasia cardia. Since its initial description, several modifications have been proposed in the technique of POEM. Broadly speaking, these modifications incorporate the basic principles of submucosal endoscopy. Key variations in the POEM technique include difference in the orientation of myotomy (anterior or posterior), length of myotomy (short or long) and thickness of myotomy (selective circular or full thickness). These modifications have been shown to reduce procedural duration without compromising the efficacy of POEM procedure. Additional modifications include preservation of sling fibers during posterior POEM and addition of NOTES fundoplication to the POEM procedure. Both these modifications intend to reduce gastroesophageal reflux after POEM. Although, some of the modified techniques have been compared with the conventional techniques in quality trials, randomized studies are awaited for others. It is likely that incorporation of some of these modifications will make POEM a technically easy and safer modality in near future. This review aims to discuss the current evidence with regards to the impact of modified techniques on the outcome of POEM.